MicroRNA-221/222 upregulation indicates the activation of stellate cells and the progression of liver fibrosis. Issue 11 (20th January 2012) - Ogawa, Tomohiro; Enomoto, Masaru; Fujii, Hideki; Sekiya, Yumiko; Yoshizato, Katsutoshi; Ikeda, Kazuo; Kawada, Norifumi
Abstract : Background: MicroRNAs (miRNAs) are important in hepatic pathophysiology and the development of liver cancer. Objective: To explore miRNAs that are regulated with the progression of liver fibrosis caused by chronic liver disease. Design: The regulated miRNAs in human livers infected with hepatitis C virus were identified by microarray analysis. Their expression in human livers with non-alcoholic steatohepatitis, mouse livers from two fibrosis models and cultured stellate cells was validated by real-time RT-PCR. The regulation of miR-222 expression in stellate cells by nuclear factor kappa B (NF-κB) was assayed. Finally, the effects of an miR-222 precursor or inhibitor on the expression of cyclin-dependent kinase inhibitor 1B (CDKN1B) and the growth of LX-2 cells were determined. Results: It was found that miR-199a-5p/199a-3p and miR-221/222 were upregulated in the human liver in a fibrosis progression–dependent manner. Among these miRNAs, miR-221/222 were upregulated in LX-2 cells and increased during the course of culture-dependent activation of mouse primary stellate cells, in a manner similar to the expression of α1(I) collagen and α-smooth muscle actin mRNAs. The expression of miR-221/222 increased in mouse models of liver fibrosis. In contrast, an NF-κB inhibitor significantly suppressed the miR-222 induction that was stimulated in culture by transforming growth factor α or tumour necrosis factor α. Although overexpression or downregulation of miR-222 failed to regulate the growth of LX-2 cells, miR-222 bound to the CDKN1B 3′UTR and regulated the expression of the corresponding protein. Conclusion: miR-221/222 may be new markers for stellate cell activation and liver fibrosis progression.